Interaction of Metamitron and Fenhexamid with Ca2+‐Montmorillonite Clay Surfaces: A Density Functional Theory Molecular Dynamics Study. Issue 14 (21st February 2019) - Belzunces, Bastien; Hoyau, Sophie; Bessac, Fabienne
Abstract : Metamitron (Meta), an herbicide, and fenhexamid (Fen), a fungicide, are authorized by the European Union to be used in agriculture. This article reports theoretical calculations about Meta and Fen in interaction with a clay surface: a Ca‐montmorillonite (Mont). Conformational searches have been performed thanks to Car–Parrinello molecular dynamics simulations from which geometries have been extracted. Interaction and adsorption energies have been calculated for isomers of Meta or Fen in interaction with Mont to understand the relative stability of various kinds of complexation. Substantial adsorption energies are comparable for Meta and Fen: around −40 kcal/mol. For Fen‐Mont, the CO monodentate family is surprisingly the lowest in energy. Moreover, the 10 lowest‐energy isomers involve complexation on Fen carbonyl oxygens. The Meta‐Mont lowest‐energy family, N‐N, does not involve π delocalization breaking within Meta. At the same time, the stronger the interaction energy is, the larger the structural modifications within Mont are, particularly concerning the interacting cation distance to the surface. The non‐negligible charge transfer and the magnitude of the adsorption energy speak in favor of the chemisorption of the pesticide on the surface. © 2019 Wiley Periodicals, Inc. Abstract : Adsorption of two pesticides, metamitron and fenhexamid, on a model for soil mineral matter (a montmorillonite surface) was studied by means of density functional molecular dynamics. For both pesticides, the non‐negligible charge transfer and the magnitude of the adsorption energy ( E ads ) suggested that the pollutant was chemisorbed on the clay surface. In both cases, the orientation of the pesticide toward the surface implied a large dispersion contribution.